Pengembangan Modul Praktikum Instalasi Penerangan Listrik di SMK Negeri 1 Talaud - Christy Oktaviani Habibu; Janles Malado (JURNAL EDUNITRO Jurnal Pendidikan Teknik Elektro, 2023)
This research is a type of research and development. The purpose of this research is to develop a practicum module on the subject of electric lighting installation at SMKN 1 Talaud. The stages carried out in this research are through five stages, namely: (i) analysis; (ii) design; (iii) development; (iv) implementation; and (v) evaluation. The final assessment of the feasibility of this practicum module obtained the following results: (i) a score from the material expert was 100%; (ii) the first design expert score was 98%; (iii) the second design expert score was 94%; and (iv) the user rating score was 98.3%. From the assessment results, the electric lighting installation practicum module is feasible to use.